Microalgae as healthy ingredients for functional food: a review. Issue 8 (6th July 2017) - Matos, J.; Cardoso, C.; Bandarra, N. M.; Afonso, C.
Abstract : Microalgae are very interesting and valuable natural sources of highly valuable bioactive compounds, such as vitamins, essential amino acids, polyunsaturated fatty acids, minerals, carotenoids, enzymes and fibre. Abstract : Microalgae are very interesting and valuable natural sources of highly valuable bioactive compounds, such as vitamins, essential amino acids, polyunsaturated fatty acids, minerals, carotenoids, enzymes and fibre. Due to their potential, microalgae have become some of the most promising and innovative sources of new food and functional products. Moreover, microalgae can be used as functional ingredients to enhance the nutritional value of foods and, thus, to favourably affect human health by improving the well-being and quality of life, but also by curtailing disease and illness risks. This review provides an overview of the current knowledge of the health benefits associated with the consumption of microalgae, bioactive compounds, functional ingredients, and health foods.